Discovery of Diaryl Ether Substituted Tetrahydrophthalazinones as TbrPDEB1 Inhibitors Following Structure-Based Virtual Screening - de Heuvel, Erik; Kooistra, Albert J.; Edink, Ewald; van Klaveren, Sjors; Stuijt, Jeffrey; van der Meer, Tiffany; Sadek, Payman; Mabille, Dorien; Caljon, Guy; Maes, Louis; Siderius, Marco; de Esch, Iwan J. P.; et al. (Frontiers in Chemistry, 2021)
Several members of the 3′,5′-cyclic nucleotide phosphodiesterase (PDE) family play an essential role in cellular processes, which has labeled them as interesting targets for various diseases. The parasitic protozoan Trypanosoma brucei, causative agent of human African trypanosomiasis, contains several cyclic AMP specific PDEs from which TbrPDEB1 is validated as a drug target. The recent discovery of selective TbrPDEB1 inhibitors has increased their potential for a novel treatment for this disease. Compounds characterized by a rigid biphenyl tetrahydrophthalazinone core structure were used as starting point for the exploration of novel TbrPDEB1 inhibitors. Using a virtual screening campaign and structure-guided design, diaryl ether substituted phthalazinones were identified as novel TbrPDEB1 inhibitors with IC50 values around 1 μM against T. brucei. This study provides important structure-activity relationship (SAR) information for the future design of effective parasite-specific PDE inhibitors.